MODELING OF PSYCHOLOGICAL SUPPORT OF PERSONS WITH DISABILITIES AT THE UNIVERSITY - Karpushkina N. V; Kisova V. V; Koneva I. A.; Kochneva E. M.; Kudryavtsev V. A.; Rossova Y. I.; Fedoseeva N. V (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article is devoted to the description of modern approaches to modeling of psychological and pedagogical support of persons with disabilities and disabilities in higher education. The article presents a model of psychological and pedagogical support of students with disabilities at the main stages of higher education, describes in detail the structural components of complex support. The aim of the study was to develop a model of psychological and pedagogical support for persons with disabilities and disabilities in the University. The targets, main directions and content of students ' support in the conditions of an inclusive University are defined. The main directions of psychological and pedagogical support of persons with disabilities and disabilities in the University are: education, diagnosis, counseling, prevention, correctional and developmental work, research (methodological) activities, etc. The article describes in detail the content of these areas for students with disabilities and disabilities. These directions are realized both in work with students, and their parents, teachers of the higher school. The modeling of psychological and pedagogical support of inclusive higher education is based on the following principles: the principle of expansion and formation of tolerant "barrier-free" space, the principle of subjectivity and socialization, the principle of motivation and activity, the principle of dialogicality, the principle of variability.